Twilight of the Merkel Era : power and politics in Germany after the 2017 Bundestag election - LANGENBACHER, ERIC (Berghahn Books, 2019)
Elections always have consequences, but the 2017 Bundestag election in Germany proved particularly consequential. With political upheaval across the globe-notably in Britain and the USA-it was vital to European and global order that Germany remain stable. And it did through the re-election of Angela Merkel as chancellor, now in her fourth term. Just under the surface, however, instability is mounting-exemplified by the entry of the right-wing Alternative for Germany (AfD) as the largest opposition party, the decline of the Social Democrats, the ever-restive Bavarians, and the growing factionalism within the Christian Democratic Union as the Merkel era comes to an end. Paying special attention to the rise of the AfD, this volume delves into the campaign, leading political figures, the structure of the electorate, the state of the parties, the media environment, coalition negotiations, and policy impacts.